REVITALISASI PENANGANAN BULLYING DI SEKOLAH: MODEL SITARA (SCHOOL INTEGRATED ANTI-BULLING RESPONE APPROACH) - Rahmat Alimin; Herawati Herawati; Sulasmi Sulasmi; Siti Suraida (JOURNAL OF EDUCATION SCIENCE, 2025)
Bullying di sekolah-sekolah Aceh terus menjadi persoalan serius dan berdampak langsung terhadap kesehatan mental, motivasi belajar, dan relasi sosial siswa. Berbagai penelitian dalam lima tahun terakhir menunjukkan bahwa praktik perundungan, baik verbal maupun fisik, masih marak dan memerlukan penanganan sistematis. Artikel ini menawarkan model konseptual SITARA (School Integrated Anti-Bullying Response Approach) sebagai pendekatan komprehensif untuk pencegahan dan intervensi bullying di sekolah Aceh. Model ini disusun melalui telaah kritis terhadap penelitian empiris terkait bullying di Aceh dan Indonesia dalam rentang 2020–2025. SITARA terdiri dari lima pilar: Screening and Mapping, Intervention and Support, Teacher Capacity Building, Awareness and Culture Building, serta Reporting and Accountability System. Model ini diharapkan menjadi rujukan bagi sekolah dalam menciptakan lingkungan belajar aman, inklusif, dan bebas kekerasan. Kata Kunci: bullying, Aceh, sekolah dasar, model intervensi, literatur review. . REVITALIZING BULLYING INTERVENTION IN ACEH SCHOOL: THE SITARA MODEL (SCHOOL INTEGRATED ANTI-BULLYING RESPONSE APPROACH) Abstract Bullying in Aceh’s schools continues to be a serious and persistent issue, directly affecting students’ mental health, learning motivation, and social relationships. Recent studies within the last five years indicate that various forms of verbal and physical bullying remain prevalent and require a systematic and culturally responsive approach. This article proposes the SITARA Model (School Integrated Anti-Bullying Response Approach) as a comprehensive conceptual framework for bullying prevention and intervention in Aceh’s educational context. Developed through a critical review of empirical studies on bullying in Aceh and Indonesia from 2020 to 2025, the model comprises five key pillars: Screening and Mapping, Intervention and Support, Teacher Capacity Building, Awareness and Culture Building, and Reporting and Accountability System. The SITARA model aims to serve as a practical reference for schools in establishing safe, inclusive, and violence-free learning environments. Keywords: bullying, Aceh, elementary schools, intervention model, literature review.